Federal and State Leadership in the Production and Delivery of Occupational Information - Worthington, Robert M.; Office of Vocational and Adult Education (ED), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Because of their concern regarding vocational education programs not being responsive to labor market conditions, the Congress has established the National Occupational Information Coordinating Committee (NOICC). The primary outcomes desired by Congress in creating NOICC were labor market supply and demand data for planning and occupational information for career and vocational decision making. These outcomes have remained essentially the same, although the participants, roles, and expectations of NOICC and the State Occupational Information Coordinating Committees (SOICCs) were greatly strengthened in 1982 and 1984. NOICC and SOICC accomplishments include SOICCs in every state and territory working with NOICC to develop and use labor market supply and demand information and access to the occupational information by millions of individuals making career decisions. The NOICC and SOICC network has developed a cooperative endeavor within and between states and among Federal agencies and worked toward standardization of occupational classification. States have become more successful in developing and implementing Career Information Delivery Systems and producing employment projections and/or supply estimates. The guidance and counseling community has the responsibility to guard the freedom of occupational and career choices and to help individuals make informed choices. Professional associations must work together to deliver occupational information effectively. (YLB)
ERIC Note: Paper presented at the National Invitational Conference on Career Counseling and Guidance in the Computer Age (Charleston, SC, October 25, 1984).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Choice; Career Counseling; Career Education; Career Guidance; Decision Making; Educational Planning; Federal Government; Federal Legislation; Federal State Relationship; Government Role; Information Systems; Labor Needs; Labor Supply; Occupational Information; Program Development; State Government; Statewide Planning; Vocational Education; National Occupational Information Coordinating Com -- State Occupational Information Coordinating Comm; Speeches/Meeting Papers; Opinion Papers